2005
DOI: 10.1590/s0102-33062005000100016
|View full text |Cite
|
Sign up to set email alerts
|

Predação de sementes ao longo de uma borda de Floresta Ombrófila Mista e pastagem

Abstract: RESUMO -(Predação de sementes ao longo de uma borda de Floresta Ombrófila Mista e pastagem). Este estudo teve como objetivo avaliar o processo de predação de sementes em três árvores nativas (Mimosa scabrella Bentham, Prunus sellowii Koehne e Myrsine laetevirens Mez.) ao longo de uma borda de Floresta Ombrófila Mista e pastagem, na Floresta Nacional de São Francisco de Paula, RS, Brasil. Grupos de sementes foram distribuídos em dez pontos aleatórios nas distâncias: 0m, 25m, 50m, 100m e 250m da borda para dentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 23 publications
1
13
0
4
Order By: Relevance
“…Second, we found a high density of E. horridum in the pasture, and this species is known to be very abundant, and outcompete previously existing species in situations where fields are managed with fire (Boldrini 1997). Third, other works performed at the study area have found high seed predation rates of woody plant species colonizing this abandoned pasture, indicating that post dispersal hazards may limit tree establishment (Baldissera & Ganade 2005).…”
Section: Discussionmentioning
confidence: 86%
“…Second, we found a high density of E. horridum in the pasture, and this species is known to be very abundant, and outcompete previously existing species in situations where fields are managed with fire (Boldrini 1997). Third, other works performed at the study area have found high seed predation rates of woody plant species colonizing this abandoned pasture, indicating that post dispersal hazards may limit tree establishment (Baldissera & Ganade 2005).…”
Section: Discussionmentioning
confidence: 86%
“…. Furthermore, recruitment and predation of seeds in the forest interior might decrease relative to edges (Baldissera and Ganade, 2005;Fleury and Galetti, 2006;Jules and Rathcke, 1999;Vargas, 1999, but see Cunningham, 2000;Guimarães and Cogni, 2002). Besides the capability of a species to perceive suitable habitat fragments and the connectivity of the landscape, its persistence in a fragmented landscape depends on its ability to cross the edge between fragment and matrix (Morris, 1997;Stamps et al, 1987a;Stevens et al, 2006).…”
Section: Habitat Edgesmentioning
confidence: 99%
“…It is of note that seed predation was greatest in areas such as the PARNASC and PESCAN, which are larger and more well-preserved. Conservation status and area size can influence seed predators, because species richness and disturbance can affect those specialized interactions (Janzen 1975;Ehrlén 1996;Pizo 1997;García et al 2000;Baldissera & Ganade 2005). Janzen (1971b;1978) suggested that mother plants increase fruit and seed production as a strategy to satiate predators and guarantee a reliable seed supply, thereby ensuring germination and consequently recruitment.…”
Section: Pre-dispersal Seed Predationmentioning
confidence: 99%
“…Studies comparing populations in terms of the occurrence of abortion and predation can further understanding of the ecological consequences to plant reproduction and persistence (Bradford & Smith 1977;Ehrlén 1996;Pizo 1997;Crawley 2000;García et al 2000García et al , 2001Steffan-Dewenter et al 2001;Leimu et al 2002;Baldissera & Ganade 2005;Marino et al 2005;Figueiredo et al 2008). In the Cerrado of Brazil, one of the most well-represented and characteristic families of woody plants is the Vochysiaceae, some species of which are among the most common and widespread in the Biome (Haridassan & Araújo 1988;Ratter et al 1996;Appolinário & Schiavini 2002;Lopes et al 2011).…”
Section: Introductionmentioning
confidence: 99%